Surgery vs non-surgery in cutaneous melanoma based on SEER database: A cross-sectional study. Issue 12 (26th March 2021) - Liu, Yingnan; Yang, Dazhi; Fu, Xiaokuan; Sun, Yulong; Xiong, Hongtao; Fang, Xichi; Zhuang, Yongqing
Abstract : Abstract: This study was to assess the survival outcome of cutaneous melanoma (CM) patients with surgery vs non-surgery through inverse probability of treatment weighting (IPTW) using the propensity score. Patients diagnosed as CM were selected from the Surveillance, Epidemiology, and End Results Program (SEER) database. The survival outcome was estimated and compared by IPTW using the propensity score. Totally 2203 CM patients were identified, in which 1921 cases received surgical treatment (surgery group), while 282 cases didn't (non-surgery group). The median survival time of surgery and non-surgery groups was respectively 150 months and 15 months (unmatched cohort), 70 months and 40 months (matched cohort) and 130 months vs. 75 months (IPTW-weighted cohort). Compared with the non-surgery group, the surgery group had a lower risk of death in unmatched [hazard ratio (HR): 0.647, 95% confidence interval (CI): 0.509–0.821, P  < .001] and matched (HR: 0.636, 95%CI: 0.459–0.882, P  < .01) cohorts. In multivariate Cox model of IPTW-weighted cohort, the risk of death in the surgery group decreased notably than the non-surgery group (HR: 0.423, 95%CI: 0.383–0.468, P  < .001). In conclusion, CM patients receiving surgical treatment are associated with a better survival outcome compared with those without surgical treatment through IPTW using the propensity score.